Mental health and development : targeting people with mental health conditions as a vulnerable group - Funk, Michelle [et al] (WHO GenevaCH, 2010)
Presents compelling evidence that people with mental health conditions meet major criteria for vulnerability. Describes how vulnerability can lead to poor mental health, and how mental health conditions are widespread yet largely unaddressed among groups identified as vulnerable.